2018
DOI: 10.1109/tie.2017.2721923
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Finite-Time Optimal Resource Management for Microgrids Based on Multi-Agent Framework

Abstract: Abstract-This paper investigates the optimal resource management in a microgrid under various operating conditions. A two-level optimization system is proposed for the distributed optimal resource management based on a multi-agent system framework. The proposed strategy generates a reference of the optimal power output at the top-level through local communication. This strategy only requires the information among neighbouring participants without a central control coordination, and simultaneously accomplishes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 36 publications
(42 reference statements)
0
33
0
1
Order By: Relevance
“…To test the scalability, in this case, we analyse the performance of the proposed restoration algorithm for the modified IEEE-39 bus system. It consists of ten DG units and the topology and specifications are provided in [43]. Before t = 2 s only primary droop control was active which results in voltage and frequency deviations.…”
Section: Case 5: Algorithm Verification With a Modified Ieee 39bus Symentioning
confidence: 99%
“…To test the scalability, in this case, we analyse the performance of the proposed restoration algorithm for the modified IEEE-39 bus system. It consists of ten DG units and the topology and specifications are provided in [43]. Before t = 2 s only primary droop control was active which results in voltage and frequency deviations.…”
Section: Case 5: Algorithm Verification With a Modified Ieee 39bus Symentioning
confidence: 99%
“…Apart from ICC-based algorithms, it is reported that distributed gradient-based methods are regarded as another popular category of distributed algorithms for solving ED problem [15][16][17][18]. Moreover, in order to design the decentralised ED algorithm with a fast convergence rate, finite-time consensus algorithms are proposed in [19,20]. However, the aforementioned spatial distributed algorithms [14][15][16][17][18][19][20] are usually applied in the static ED problems of MG, which are limited to the fixed scheduling plan during one period and cannot respond to unexpected variability of RES in a long term [21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in order to design the decentralised ED algorithm with a fast convergence rate, finite-time consensus algorithms are proposed in [19,20]. However, the aforementioned spatial distributed algorithms [14][15][16][17][18][19][20] are usually applied in the static ED problems of MG, which are limited to the fixed scheduling plan during one period and cannot respond to unexpected variability of RES in a long term [21]. In recent years, the alternating direction method of multipliers (ADMM) algorithm has also been applied to the decentralised optimisation of distribution networks.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, distributed optimisation has attracted more and more attention with the development of network technology [1, 2]. It has been widely used in distributed computation [3], sensor network [4, 5], power systems [6, 7] and so on. Compared to traditional optimisation methods, distributed optimisation enables a transition from the centralised framework to the distributed framework.…”
Section: Introductionmentioning
confidence: 99%